Nitrate triggered phosphoproteome changes and a PIN2 phosphosite modulating root system architecture. (6th August 2021) - Vega, Andrea; Fredes, Isabel; O'Brien, José; Shen, Zhouxin; Ötvös, Krisztina; Abualia, Rashed; Benkova, Eva; Briggs, Steven P; Gutiérrez, Rodrigo A
Abstract: Nitrate commands genome‐wide gene expression changes that impact metabolism, physiology, plant growth, and development. In an effort to identify new components involved in nitrate responses in plants, we analyze the Arabidopsis thaliana root phosphoproteome in response to nitrate treatments via liquid chromatography coupled to tandem mass spectrometry. 176 phosphoproteins show significant changes at 5 or 20 min after nitrate treatments. Proteins identified by 5 min include signaling components such as kinases or transcription factors. In contrast, by 20 min, proteins identified were associated with transporter activity or hormone metabolism functions, among others. The phosphorylation profile of NITRATE TRANSPORTER 1.1 ( NRT1.1) mutant plants was significantly altered as compared to wild‐type plants, confirming its key role in nitrate signaling pathways that involves phosphorylation changes. Integrative bioinformatics analysis highlights auxin transport as an important mechanism modulated by nitrate signaling at the post‐translational level. We validated a new phosphorylation site in PIN2 and provide evidence that it functions in primary and lateral root growth responses to nitrate. Synopsis: Phosphoproteomic analysis in response to nitrate treatment reveals early nitrate‐induced changes in Arabidopsis thaliana root phosphoproteins associated to signaling while late changes are associated to transport and hormone metabolism. Moreover, nitrate promotes the dephosphorylation of PIN2, impacting PIN2 subcellular localization and root development. Several nitrate‐regulated phosphoproteins involved in signaling, metabolism and other functions were identified. NRT1.1 is required for normal phosphoproteome responses to nitrate treatments. Nitrate regulates root system architecture by modulating PIN2 phosphorylation status. Abstract : Phosphoproteomic analysis in response to nitrate treatment reveals early nitrate‐induced changes in Arabidopsis thaliana root phosphoproteins associated to signaling while late changes are associated to transport and hormone metabolism. Moreover, nitrate promotes the dephosphorylation of PIN2, impacting PIN2 subcellular localization and root development.